Preliminary tests of obtaining shape memory alloy thin layer through PLD technique - VIZUREANU, Petrica (Journal of Mining and Metallurgy, Section B: Metallurgy, 2014)
Abstract . A shape memory alloy based on copper was obtained through a classic melting method. The material was analyzed in heat treated and deformed states through scanning electrons microscopy (SEM), dilatometry (DIL), differential scanning calorimetry (DSC) , dynamic mechanical analyzer (DMA) and energy dispersive X-ray analyze (EDAX) to establish the material microstructure, memory properties like martensitic transformation domain and rate or damping capacity. The material exhibits a good shape memory effect and high internal friction and it is proposed as target in a pulsed laser deposition process for obtaining thin films. The deposition process is described in this paper and few experimental results on the layer are presented.